ANALISIS GENDER TERHADAP PERAN ISTRI DALAM MENJALANKAN FUNGSI KELUARGA: Studi Pasangan Keluarga Jarak Jauh di Purwokerto, Kabupaten Banyumas - falah, Nabilah (Musawa: Journal for Gender Studies, 2023)
Women are often burdened with carrying out family functions, especially for long-distance partners. This is due to the gender bias that grows in society and places women with feminine characteristics in the domestic sector, while men with masculine characteristics are placed in the public sector. This article tries to explain the role of the wife in carrying out family functions for long-distance family couples, especially for informants in the city of Purwokerto. This type of research is field research using a gender approach to determine the existence of gender bias that occurs in the distribution of family function roles. Primary data obtained from interviews was then analyzed qualitatively. Based on the research results, it can be concluded that the role of husband and wife in carrying out family functions in long-distance couples in Purwokerto is mostly carried out by women as wives, which causes women to experience multiple burdens. This is due to the patriarchal culture and government policies which seem to place women in a domistic position and are responsible for everything that happens in their household.